Pengaruh Disiplin Kerja dan Lingkungan Kerja terhadap Kinerja Karyawan Bagian Operator Produksi pada PT. Multi Makanan Tebet Barat - Muhamad Guruh; Fitri Sabina; Surya Budiman (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
Employee performance is one of the key factors that determines the success of a company in achieving organizational goals. In the manufacturing industry, work discipline and work environment play an important role in improving employee productivity and effectiveness. Low work discipline may lead to delays, reduced productivity, and non-compliance with company regulations, while an unfavorable work environment can decrease employee comfort, motivation, and work efficiency. Therefore, companies need to maintain employee discipline and create a supportive work environment to optimize employee performance. This study aims to analyze the effect of work discipline and work environment on employee performance at PT Multi Makanan Tebet Barat, both partially and simultaneously. This research employed a quantitative approach using a survey method. The study was conducted at PT Multi Makanan Tebet Barat, located in Sukadami, Wanayasa District, Purwakarta Regency, West Java 41174. The respondents consisted of 85 employees selected through a census sampling technique. Data were collected through the distribution of Likert-scale questionnaires. The data were processed using SPSS version 27 and analyzed using multiple linear regression analysis. The results indicate that work discipline and work environment have positive and significant effects on employee performance, both partially and simultaneously.